Non-invasively assessed skeletal bone status and its relationship to the biomechanical properties and condition of cancellous bone - Cook, R. B. (Cranfield University, 2005)
Cancellous bone constitutes much of the volume of bone which makes up axial skeletal sites such as the vertebrae of the spine and the femoral neck. However the increased vascularity of cancellous bone compared with cortical bone means that it is more prone to drug, endocrine and metabolic related effects and therefore these skeletal sites are more prone to the bone condition osteoporosis. With the bone condition osteoporosis increasing in prevalence it is becoming far more important not only for those at risk of having the condition to be diagnosed earlier, but also for the effects of the condition to be better understood. There is a need for the better clinical management of fractures and for therapies and medical practices that will best avoid the low trauma fractures that are seen as a consequence of the condition. This study is in two separate sections, the first constitutes an investigation into the diagnostic abilities of the CUBA Clinical and Sunlight Omnisense quantitative ultrasound systems; and on the other hand an examination of the osteoporotic risk factor questionnaires, Osteoporosis Risk Assessment Instrument (ORAI), Osteoporosis Index of Risk (OSIRIS), Osteoporosis Self-assessment Tool (OST), Patient Body Weight (pBW), Simple Calculated Osteoporosis Risk Estimation (SCORE) and the Study of Osteoporotic Fractures (SOFSURF). The skeletal status was assessed by DXA at the axial skeleton. The aim was to differentiate between the systems that could rationally be used to screen populations to identify those who needed DXA densitometry investigations, on the basis of ability. The second section of the study focused on the biomechanics of cancellous bone, with the initial studies examining the compressive properties of both osteoporotic and osteoarthritic cancellous bone and the effects that the conditions have on the compressive mechanics of the bone. The later section is the first ever study into the K, G and J-integral fracture mechanics of cancellous bone. It used osteoporotic and osteoarthritic cancellous bone from the femoral head of a cohort of ultrasound scanned patients and of some equine vertebral cancellous bone. The study focused on the identification of the dominant independent material variables which affected the compressive and fracture mechanics of cancellous bone, and the differences that were seen between the two different skeletal conditions. In addition to the independent variables, quantitative ultrasound (QUS) scans were performed on the donors of the femoral heads which enabled investigation into QUS’s ability to predict either the compressive or fracture mechanics of bone in-vivo. The study demonstrated that the investigation of the calcaneus using the CUBA clinical system provided the highest level of diagnostic accuracy (AUC: 0.755 - 0.95), followed by the questionnaires, of which the OSIRIS questionnaire was the best performer (AUC: 0.74 – 0.866), and lastly the Sunlight Omnisense results. The best option for the prediction of the lowest feasible DXA T-score was a combination of the CUBA Clinical results, the individual’s weight and the OSIRIS questionnaire (r2 = 45.5%), with potential minor, but significant, support also added by the OST and SOFSURF questionnaires (r2 = 46.8%). The compressive testing demonstrated that osteoporotic and osteoarthritic bone both performed differently with respect to the apparent density, with the osteoporotic bone adhering to the previously published power function relationships, but with the osteoarthritic bone having lower power functions. The stress intensity factor for plane strain testing (KQ or KC) and the critical strain energy release rate results were both influenced primarily by the apparent density with the K values obeying a power relationship to the power of 1.5 and G a relationship to the power 2. However, both the composition and integrity of the collagen network, (demonstrated by collagen cross-link analysis), played roles in the explanation of the fracture mechanics results. The J-integral results were distinctly different to those of the K and G results with regard to their dependence on composition and it is hypothesised that this is due to the structure of the bone having more dominant effects than the apparent density. In conclusion, the fracture mechanics of cancellous bone are contributed to by a complex combination of a number of variables, but with apparent density dominating the K and G fracture mechanics to a power function of between 1 and 2. Currently available QUS systems demonstrated an ability to relate to the Young’s modulus and strength but also, in this study, to the fracture mechanics variables of the cancellous bone from the hip. This relationship is a profound outcome which may help the clinical management of the condition and the fractures when they occur. The dependence on fracture mechanic variables points to a clear causal relationship between the bone fracture parameters and bone condition as underlying factors of osteoporotic fractures.
Keywords: Bone; Cancellous bone; Fracture mechanics; Osteoporosis